Historical and Religious Site as Tourism Attraction: The Case of the Demak Great Mosque - Susilowati, Indah; Ayu Kusumawardhani, Hapsari; Wardhani, Arisanti Ayu; Islam, Gazi Md Nurul; Febrianti , Anisa Millenia; Pungkasa, Yeremia Satrya (KARSA Journal of Social and Islamic Culture, 2023)
Historical and religious sites are developing into tourist attractions. Tourist perception is interpreted as one way to determine visitor satisfaction, can advance the improvement of tourist attractions, and is a driver for revisit intentions. This study aims to explore the views of tourists regarding the meaning of the religious and historical as a tourist attraction, the pattern of visitor density in the tourist area of the Great Mosque of Demak, and to identify the perception of tourists about facilities, and revisit the intention of the Demak Great Mosque. The photovoice method is used to answer the meaning of Demak Great Mosque visitors from November to December 2022. The participants in the photovoice method were 12. The second method is the descriptive quantitative to answer objectives 2 and 3. The sample of this study was 104 respondents. All the tourist respondents collected multistage sampling. The results of this study indicate that the Demak Great Mosque is an attraction for historical, religious and educational tourism. In the tourist object area, the Great Mosque of Demak has the highest density in the high and low seasons. Tourist perceptions of the quality of religious and non-religious facilities. This means that the Great Mosque of Demak already has a capacity for facilities that satisfy visitors. The mosque's architecture attracted the majority of tourists and least of all, they consider the lack of shelter from the hot sun. The intention of visitors to return to the Great Mosque of Demak is 89.42%.